Efektivitas Penyuluhan Kesehatan Hipertensi Terhadap Tingkat Pengetahuan Masyarakat Sukasukur Kelurahan Kersanagara - Purnama, Ade Siska; Nurani, Dewi; Nurfaujiyah, Neneng Wanda; Zahira Sofa, Ghaitsa; Murnita, Fitri; Nirmala, Resvia; Unisah, Icah; Gumilar, Handi; Insani, Naufal; Wahyudi, Salman; Aljabbari, Iman Syarifuddin (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction : Village health community development activities (PKMD) were carried out in the RT 03 RW 05 area of ​​Kersanagara Village, Tasikmalaya City starting from March 5-13, 2025. The series of activities included health education on hypertension. Hypertension is a degenerative disease where blood pressure exceeds the normal limit, which is >120/80 mmHg. People with hypertension can control their blood pressure independently anywhere and anytime. Seeing this condition, health education on hypertension is needed to prevent unwanted complications. Objective : To increase public knowledge about hypertension and to carry out prevention for themselves and their families. Method : This activity is carried out using lecture methods, discussions, giving Pre-Test and Post-Test questions, and questions and answers. Result : Before health education about hypertension, the level of public knowledge was 60%, and after health education was given, it increased to 90%. This shows that there is an influence of hypertension health education on increasing public knowledge. Conculsion : The results of the activity evaluation showed a significant increase in knowledge. This activity was fully supported by the Kernagara Village and Kersanagara Health Center. This activity also showed benefits for extension workers in developing communication skills and for the community who better understand hypertension, and showed the success of the Village Community Health Development program to improve community understanding in the area.